2007
DOI: 10.1007/s11274-007-9600-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities of methanol extracts of Evax pygmaea (Asteraceae) growing wild in Tunisia

Abstract: Antimicrobial activity of methanolic extracts obtained from the aerial parts of Evax pygmaea was tested against five bacteria and two strains of phytopathogenic fungi using the agar diffusion and broth microdilution methods. Antioxidant properties were evaluated through the ability of the different fractions to scavenge the stable ABTS (2,2 0 -azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)) and DPPH (1,1-dip henyl-2-picrylhydrazyl) radicals. The TEAC (Trolox Equivalent Antioxidant Capacity) and IC 50 values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
3
22
0
1
Order By: Relevance
“…The antioxidant activities measured in the TEAC assay also significantly correlate with the DPPH IC 50 value (r 2 = 0.92), as shown in Figure 3(b). This finding, which indicated that both the DPPH IC 50 value and the TEAC assay could be used simultaneously to determine the antioxidant activities of Allium extracts, is supported by the findings of many other similar experiments [9,14,22,23].…”
Section: Correlation Analysis Of the Dpph Ic 50 Value Total Phenolicsupporting
confidence: 79%
See 2 more Smart Citations
“…The antioxidant activities measured in the TEAC assay also significantly correlate with the DPPH IC 50 value (r 2 = 0.92), as shown in Figure 3(b). This finding, which indicated that both the DPPH IC 50 value and the TEAC assay could be used simultaneously to determine the antioxidant activities of Allium extracts, is supported by the findings of many other similar experiments [9,14,22,23].…”
Section: Correlation Analysis Of the Dpph Ic 50 Value Total Phenolicsupporting
confidence: 79%
“…The experiments were run in triplicate, and the developing inhibition zones were compared with those of the reference discs. In addition, the minimal inhibitory concentration (MIC) of the samples was determined by the broth dilution method using the serially diluted Allium extracts as described [6,9]. Then, bacterial cultures were prepared in a nutrient broth and incubated at 37˚C for 24 h. The bacterial cultures were adjusted with sterilized saline to bring the concentration to 10 7 mL −1…”
Section: Assay Of Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…These strains were purchased from the Bioresource Collection and Research Center of the Food Industry Research Institute in Hsinchu City, Taiwan. A tube dilution test [15] and an agar disc diffusion test [16] [17] were performed to study the antifungal activity of A. fistulosum extracts against the aforementioned seven fungal strains. Fifty microliters of the A. fistulosum extract at 1 mg/ml was applied to an ethanol-sterilized paper disc (8 mm in diameter) and placed onto the PDA agar plates.…”
Section: Antifungal Activity Of Taiwanese a Fistulosummentioning
confidence: 99%
“…(Asteraceae) that was the most active against S. aureus; while, the chloroform extract resulted less potent against the Gram-positives S. epidermidis and Micrococcus luteus (Boussaada et al 2008).…”
Section: Antibacterial Activitiesmentioning
confidence: 99%